5.7k views
1 vote
Pls solve 2(3 - x) -12 + 4x = -3x -9

User DiegoDD
by
4.7k points

2 Answers

7 votes

Answer:

x=-3/5

Explanation:


2(3-x)-12+4x=-3x-9


6-2x-12+4x=-3x-9


-6+2x=-3x-9


2x+3x=-9+6


5x=-3


x=(-3)/(5)

User VdesmedT
by
6.1k points
3 votes

Answer:

x = -3/5

Explanation:

2(3 - x) -12 + 4x = -3x -9

Distribute

6 -2x -12 +4x = -3x -9

Combine like terms

2x -6 = -3x -9

Add 3x to each side

2x+3x -6 = -3x+3x -9

Add 6 to each side

5x -6+6 = -9+6

5x = -3

Divide each side by 5

5x/5 = -3/5

x = -3/5

User James Strachan
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.